Performance and microbial characterization of two-stage caproate fermentation from fruit and vegetable waste via anaerobic microbial consortia. (July 2019) - Yu, Jiangnan; Huang, Zhenxing; Wu, Peng; Zhao, Mingxing; Miao, Hengfeng; Liu, Chunmei; Ruan, Wenquan
Graphical abstract: Highlights: Sufficient FVW degradation and more acetate formation was gained by optimizing ISR. High caproate yield and selectivity were achieved by regulating E/A ratio and pH. The mixed culture caproate fermentation was dominated by C. kluyveri . Caproate was mainly generated in the middle and late stages of C. kluyveri growth. Abstract: The regulation of two-stage caproate fermentation from fruit and vegetable waste (FVW) via anaerobic microbial consortia was investigated in this study. The results showed the highest caproate production achieved 14.9 g/L at the optimal inoculum to substrate ratio (ISR) of 2:1, ethanol to acid ratio (E/A) of 4:1, and pH of 7.5. The caproate yield and selectivity respectively reached 0.62 g/g and 80.8% (as COD). In acidification stage, an appropriate ISR provided a high conversion efficiency and more acetate formation, which was beneficial to caproate biosynthesis. In caproate production stage, chain elongation performance was sensitive to E/A and pH condition. Butyrate became the main by-product at low E/A or acidic conditions, while excessive ethanol or alkaline condition seriously suppressed substrate conversion. The caproate fermentation was dominated by Clostridium kluyveri . Furthermore, caproate formation was uncoupled with Clostridium kluyveri proliferation, which was mainly generated during the middle and late stages of growth.